Shakespeare’s Great Tragedies - Md. Shafiqul Islam (Crossings, 2009)
Mohit Ul Alam has accomplished a splendid job for those who want to read Shakespeare’s great tragedies in Bangla. He completed with virtuosity his arduous but praiseworthy task by presenting us with Bangla renditions of Shakespeare’s great plays in one edition: Hamlet, Othello, King Lear and Macbeth…